Analysis of Innovation Culture, Entrepreneurial Leadership, Brand Image and Competitive Advantage as Intervening Variables on PT XX Company Performance - Kartini, Fenny; Syafarudin, Afriapollo; Nurmahdi, Adi (PT FORMOSA CENDEKIA GLOBAL, 2024)
In general, this research was conducted to serve as material for analyzing innovation culture, entrepreneurial leadership, brand image, and competitive advantage as intervening variables affecting the performance of PT XX, which is part of a national company group located in the Tangerang area with 200 permanent workers. The data analysis was performed using the Structural Equation Model (SEM) approach based on Partial Least Squares (PLS) 3.0, with hypothesis testing conducted on 110 samples. The results of the study show that innovation culture, entrepreneurial leadership, and brand image associated with high-quality products can influence competitive advantage as intervening variables, so that they can be assessed as having an effect on improving the Performance of PT XX. However, this impact requires a management strategy characterized by commitment and consistency to achieve the desired outcomes.